Mutations in the Drosophila homolog of human PLA2G6 give rise to age-dependent loss of psychomotor activity and neurodegeneration. - Iliadi, K.G.; Gluscencova, O.B.; Iliadi, N.; Boulianne, G.L. (Scientific reports, 2018)
Infantile neuroaxonal dystrophy (INAD) is a fatal neurodegenerative disorder that typically begins within the first few years of life and leads to progressive impairment of movement and cognition. Several years ago, it was shown that >80% of patients with INAD have mutations in the phospholipase gene, PLA2G6. Interestingly, mutations in PLA2G6 are also causative in two other related neurodegenerative diseases, atypical neuroaxonal dystrophy and Dystonia-parkinsonism. While all three disorders give rise to similar defects in movement and cognition, some defects are unique to a specific disorder. At present, the cellular mechanisms underlying PLA2G6-associated neuropathology are poorly understood and there is no cure or treatment that can delay disease progression. Here, we show that loss of iPLA2-VIA, the Drosophila homolog of PLA2G6, gives rise to age-dependent defects in climbing and spontaneous locomotion. Moreover, using a newly developed assay, we show that iPLA2-VIA mutants also display impairments in fine-tune motor movements, motor coordination and psychomotor learning, which are distinct features of PLA2G6-associated disease in humans. Finally, we show that iPLA2-VIA mutants exhibit increased sensitivity to oxidative stress, progressive neurodegeneration and a severely reduced lifespan. Altogether, these data demonstrate that Drosophila iPLA2-VIA mutants provide a useful model to study human PLA2G6-associated neurodegeneration.